Pengaruh Lokasi dan Kualitas Pelayanan terhadap Keputusan Nasabah untuk Menabung di BMT Sumber Mulia Tuntang - Tyas, Rizqa Ramadhaning; Setiawan, Ari (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
This study discusses the influence of the quality of services consisting ofreliability, responsiveness, assurance, empathy and tangibles as well as thelocation of BMT and variables are the most significant influence on thecustomer’s decision to save in BMT Sumber Mulia. The method used in thisstudy is a quantitative approach, with the amount of the sample was 30respondents. The sampling technique used accidential sampling by applyingis linear regression analysis, which previously conducted validity and reliability. Based on these results, we can conclude. First, there was a significant effect of the quality of service which consists of reliability, responsiveness, assurance, empathy, and tangibles on saving decisions. This is evident from the results of the t test with a value of t count t table at the 5% significance level reliability (3.838 1.7011), responsiveness (2.121 1.7011), assurance (3.062 1.7011), empathy (4.760 1.7011), and tangibles (3.290 1.7011). There is a significant influence on the customer decision to save their money in BMT. Based on it location as the t test results are t count t table (3.480 1.7011), with a significance level of 5%. Third, empathy variables are variables that provide the dominant influence on the customer’s decision to saving. It can be seen from the significance value (0.000) is more significant than other variables. Then proceed with the reliability variables with a significance value (0.001), the variable of location (0,002), tangibles (.003), assurance (0.005) and responsiveness with a significance value (0.043). This means that the willingness of employees and managers are more concerned with to draw customer attention on saving their money